2019
DOI: 10.1155/2019/6264931
|View full text |Cite
|
Sign up to set email alerts
|

Notch3 Targeting: A Novel Weapon against Ovarian Cancer Stem Cells

Abstract: Notch signaling is frequently activated in ovarian cancer (OC) and contributes to the proliferation and survival of cultured OC cells as well as to tumor formation and angiogenesis in xenograft models. Several studies demonstrate that Notch3 expression renders cancer cells more resistant to carboplatin, contributing to chemoresistance and poor survival of OC-bearing patients. This suggests that Notch3 can represent both a biomarker and a target for therapeutic interventions in OC patients. Although it is still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 70 publications
1
21
0
Order By: Relevance
“…Several elements of the Notch pathway were markedly down-regulated and further experimental validation suggested that this downregulation was not consequence but rather a contributor to the senescence program activated by BMS. Notch signaling plays a crucial role during embryonic development and cancer 26 , and its inhibition has been proposed as a potential anti-cancer therapy 36,37 In our hands, activation of the pathway using a recombinant ligand abrogated the pro-senescence effect of BMS. This finding can be highly relevant since the Notch pathway may play a role in the pathogenesis of RA.…”
Section: Discussionmentioning
confidence: 75%
“…Several elements of the Notch pathway were markedly down-regulated and further experimental validation suggested that this downregulation was not consequence but rather a contributor to the senescence program activated by BMS. Notch signaling plays a crucial role during embryonic development and cancer 26 , and its inhibition has been proposed as a potential anti-cancer therapy 36,37 In our hands, activation of the pathway using a recombinant ligand abrogated the pro-senescence effect of BMS. This finding can be highly relevant since the Notch pathway may play a role in the pathogenesis of RA.…”
Section: Discussionmentioning
confidence: 75%
“…The above data represent the mean ± SD of three independent experiments. ***, P < 0.001; **, P < 0.01; *, P < 0.05, t test Although c-Kit has been reported to collaborate with Notch signaling in regulating multiple cellular functions [45][46][47], it is unclear whether c-Kit can regulate or activate Notch3, which plays an important role in CSC [34,35,48,49] and high-grade ovarian serous carcinoma [50][51][52][53]. In our study, we found that c-Kit, Notch3 and raft-phospho-PHB protein expression were enhanced in our generated metastatic phenotypes of SKOV3 cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Since c-Kit and Notch3 have been reported to play a role in the regulation of ovarian CSCs [19,34,35] and CSC-driven metastasis [36,37], we examined their expression in these different phenotypes of SKOV3GL cells. Our results showed that c-Kit, full-length (FL) Notch3 and membrane-tethered Notch3 fragment (NTM) expression were all significantly increased in SKOV3GL-G3 and SKOV3GL-G4 cells (Fig.…”
Section: Metastatic Phenotypes Of Skov3 In Xenograft Murine Ascites Smentioning
confidence: 99%
“…Aberrant activation of the Notch signalling pathway has been implicated in numerous human malignancies, including EOC [ [44] , [45] , [46] , [47] ]. Particularly, the amplification of the chr19p13.12 region ( Notch3 ) and its up-regulation at mRNA and protein levels have been detected in a large percentage of OC [ 48 , 49 ]. Another example of alteration in this pathway is the CXCR4/SDF1α chemokine system, which plays a key role in EOC cell biology [ 50 ].…”
Section: Proliferation and Cell Growthmentioning
confidence: 99%